HUBUNGAN KEPATUHAN PENGOBATAN ANTIHIPERTENSI DENGAN RISIKO KARDIOVASKULAR PADA PASIEN HIPERTENSI PUSKESMAS TELAGA MURNI - Antarini, Destya; Marselina, Marselina; Adiwisastra, Nuzul Gyanata; Suparmi, Ninik (Jurnal Buana Farma, 2025)
Hypertension is a major risk factor for cardiovascular disease, with its prevalence continuously increasing in the community. Adherence to antihypertensive therapy plays a crucial role in controlling blood pressure and preventing cardiovascular complications. However, evidence on the relationship between medication adherence and cardiovascular risk remains inconsistent, especially in primary healthcare settings. This study was conducted at Telaga Murni Primary Health Center – Cikarang, where hypertension is among the ten most common diseases. The study aimed to determine the relationship between adherence to antihypertensive therapy and cardiovascular risk among hypertensive patients. This research employed a quantitative analytic design with a cross-sectional approach involving 85 hypertensive patients selected through purposive sampling. Adherence was assessed using the Medication Adherence Report Scale (MARS-5) and Medication Possession Ratio (MPR), while cardiovascular risk was evaluated using the ASCVD Risk Estimator. Data were analyzed using the Chi-Square test, linearity test, and Odds Ratio calculation. The results showed that most patients were adherent (MARS-5 = 91.8%; MPR = 72.9%) and had low cardiovascular risk (52.9%). There was a significant relationship between adherence and cardiovascular risk for both MARS-5 (p=0.041) and MPR (p=0.049), although linear correlation was observed only in MARS-5 (p=0.012). Adherent patients had a higher likelihood of having a lower cardiovascular risk compared to non-adherent patients. In conclusion, adherence to antihypertensive therapy was associated with cardiovascular risk among hypertensive patients. Continuous education and regular monitoring are essential to maintain patient adherence and prevent increased cardiovascular risk.